A 400, 000‐year‐old mitochondrial genome questions phylogenetic relationships amongst archaic hominins. (6th April 2014) - Orlando, Ludovic
<x xml:space="preserve">Abstract</x> By combining state‐of‐the‐art approaches in ancient genomics, Meyer and co‐workers have reconstructed the mitochondrial sequence of an archaic hominin that lived at Sierra de Atapuerca, Spain about 400, 000 years ago. This achievement follows recent advances in molecular anthropology that delivered the genome sequence of younger archaic hominins, such as Neanderthals and Denisovans. Molecular phylogenetic reconstructions placed the Atapuercan as a sister group to Denisovans, although its morphology suggested closer affinities with Neanderthals. In addition to possibly challenging our interpretation of the fossil record, this study confirms that genomic information can be recovered from extremely damaged DNA molecules, even in the presence of significant levels of human contamination. Together with the recent characterization of a 700, 000‐year‐old horse genome, this study opens the Middle Pleistocene to genomics, thereby extending the scope of ancient DNA to the last million years.